A Conformer‐Dependent, Quantitative Quadrant Model. Issue 17 (21st April 2021) - Zahrt, Andrew F.; Rinehart, N. Ian; Denmark, Scott E.
Abstract: This study reports the development and application of a conformer‐dependent quantitative quadrant descriptor for generating models that relate catalyst performance to catalyst structure in enantioselective transformations. The generality of these descriptors is demonstrated by using them for three different reactions: (1) copper‐catalyzed, enantioselective cyclopropanation of alkenes, (2) rhodium‐catalyzed enantioselective hydrogenation of α ‐substituted N ‐acyl‐enamides, and (3) enantioselective addition of thiols to N ‐acyl imines. This work will provide researchers an interpretable steric descriptor that merges the heuristic value of quadrant models with a quantitative tool that can be used to create statistically meaningful correlations between the steric occupancy of catalyst quadrants and stereoselectivity. The low dimensionality of this descriptor, its ability to capture conformational effects and stereostructure, and its direct relationship to intuitive structural properties make it particularly well‐suited for creating Quantitative Structure‐Selectivity Relationships (QSSR) with smaller datasets of asymmetric reactions. Abstract : A conformer‐dependent, quantitative quadrant descriptor has been developed. This descriptor can be used to generate regression models relating catalyst selectivity to catalyst stereostructure. This descriptor merges the heuristic value of the quadrant model with a quantitative tool to model catalyst stereoselectivity.